The Problem of Religious Intolerance: A Theological Approach to Justice and Tolerance in Indonesia (Indonesian Theological Justice Review, 2025)
Religious intolerance remains a significant challenge in Indonesia’s diverse society, where tensions between religious groups have led to conflicts and human rights violations. This paper examines the theological underpinnings of religious tolerance and its role in promoting justice in Indonesia. By analyzing Islamic, Christian, and indigenous religious perspectives on interfaith relations, the study explores how religious teachings can foster understanding and peaceful coexistence among different faith communities. The paper investigates theological concepts such as the Islamic principle of "ahimsa" (peaceful coexistence), Christian notions of love and reconciliation, and indigenous values of harmony with others. The research highlights the ways in which religious leaders, scholars, and institutions can contribute to combating intolerance through religious education, interfaith dialogues, and public advocacy. However, the paper also addresses the challenges posed by political interests, radical religious movements, and sectarian violence. It argues that theology, with its emphasis on universal human dignity and justice, can be a powerful tool for promoting religious tolerance and addressing the root causes of intolerance. Recommendations include incorporating interfaith dialogue into religious education curricula, supporting faith-based initiatives for tolerance, and promoting theological reflections on justice as it relates to religious pluralism.